LEARNING TO BELONG: AFGHAN NEWCOMER CHILDREN AND THE SOCIAL FABRIC OF AMERICAN SCHOOLS - Siddiqui, Munawar (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2025)
There are important psychological, social, and cultural issues involved in the assimilation of Afghan refugees into American society. After the U.S. exited Afghanistan, Afghan refugees were temporarily detained in camps before being relocated around the U.S. Although they have survived the immediate danger, the impact of war, displacement, and detention has resulted in the refugees suffering chronic psychological trauma including PTSD, anxiety, and depression. These mental health conditions, along with cultural differences and difficulty acclimating to American social customs, add a layer of complication to the integration process.In this paper, the most important issues confronting foreign refugees are analyzed, and field-tested policy recommendations that can help to reconstruct and integrate this population into American life are formulated. The study employs a combination of methods such as interviews, surveys, focus groups, and case studies to better understand the experiences of Afghan refugees and the opinions of the American host communities.Results show that there are strong societal concerns toward refugee integration that can, however, be overcome by well-organized supporting measures. Other recommendations include gradual acclimation to the community, compulsory psychosocial support, and the development of cultural awareness programs for both refugees and host populations. Furthermore, targeted educational bridging programs are proposed for refugee children, aimed at covering the educational gap and supporting emotional development.It is particularly important to have mechanisms for continued monitoring of integration outcomes in the long term so that refugees are not left behind and are encouraged as they adjust to stable lives. The U.S. can make it easier for Afghans to be absorbed into society with the right policy recommendations in place. Given long-term planning and consistent support, refugees are able to start afresh and contribute to the social and cultural tapestry of this country.